Cancer Pain Management and Pain Interference with Daily Functioning among Cancer Patients in Gondar University Hospital - Henok Getachew Tegegn; Eyob Alemayehu Gebreyohannes (Pain Research and Management)
Cancer is an increasing public health burden for Ethiopia. Pain is among the most common symptoms in patients with cancer. Hence, we aimed to assess cancer pain prevalence, cancer pain interference, and adequacy of cancer pain treatment in the oncology ward of an Ethiopian teaching hospital. Of 83 patients, total of 76 (91.6%) cancer patients experienced pain with varying degree of severity, and 7 (8.4%) patients experienced severe pain. Of the 76 cancer patients with pain, 68 (89.2%) experienced pain interference with their daily activities. Fifty-four (65%) patients were receiving inadequate cancer pain treatment with negative Pain Management Index. Therefore, it is vital to anticipate and assess pain of the cancer patients as routine clinical practice, to optimize analgesic therapy, and to identify and overcome barriers to adequate pain management.